Городские монастыри византийского Херсона: к постановке проблемы - Яшаева, Т.Ю. (Материалы по археологии, истории и этнографии Таврии, 2007)
Важным признаком структуры средневекового города, принципиально отличающим его от античного полиса, были монастыри. В истории восточно-христианского монашества можно выделить три периода расцвета, сопровождавшихся активизацией монастырского строительства, в том числе городского. The author distinguishes three fiourishing periods in the history of Eastern-Christian monasticism: Justinian period, Post-iconoclasm and Palaeologus period. City monasteries of Cherson are examined in the article in accordance with these periods. The author develops the combination of characteristics, main and minor, that would enable to mark a monastery out of Cherson’s urban buildings. There are two tendencies in Cherson’s city monastery topography: sacral centers and city outskirts are very close to the defensive walls and the walls are used as a monastery fence. Cherson’s monastery complexes were quite small in size and number comparatively to other Eastern-Christian centers and did not have unified standard planning. According to the tradition of local urban building they were put down into already existed living quarters. One of the actual questions of modern Christian Cherson archaeology is picking out monasteries and monastery structures connected to them out of city building during the new sites discovery as well as while giving a new meaning to the old ones.